Incidence of Catheter-Related Infections in Maintenance Hemodialysis Patients: A Critical Challenge in Balochistan, Pakistan - Wali, Abdul; Khan, Dilawar; Mohkumuddin, Syed; Aslam, Farooq; Khan, Saifuddin; Din, Sajidud (Pakistan Journal of Kidney Diseases, 2025)
Background: Catheter-related infections (CRIs) represent a critical complication in haemodialysis patients, particularly in resource-limited settings. This study investigated the incidence, risk factors, and predictors of CRIs among haemodialysis patients at Sandeman Provincial Hospital, Quetta, Balochistan, Pakistan. Methods: A cross-sectional observational study was conducted from January 2023 to December 2024, enrolling 357 adult patients with end-stage renal disease undergoing maintenance haemodialysis via central venous catheters. Data were collected using structured questionnaires covering demographics, clinical parameters, catheter characteristics, and institutional factors. Statistical analyses included descriptive statistics, chi-square tests, Mann-Whitney U tests, logistic regression, and Kaplan-Meier survival analysis. Results: The CRI incidence was exceptionally high at 82.1% (293/357 patients), with exit-site infections predominating (96.2%) and catheter-associated bloodstream infections accounting for 22.9%. Diabetes mellitus emerged as the strongest predictor (adjusted OR = 6.3, P < 0.001), followed by non-sterile gauze use (OR = 4.2) and hypertension (OR = 3.1). Femoral catheters were associated with higher bloodstream infection rates compared to subclavian access (P = 0.023). Critical institutional gaps included suboptimal hand hygiene compliance (73%), minimal staff training rates (2.2-10.9%), and zero utilization of antibiotic lock therapy. Conclusions: CRI rates at this facility far exceed international benchmarks, driven by modifiable patient-specific, procedural, and institutional factors. Urgent implementation of evidence-based interventions including improved infection control protocols, staff training, and catheter care bundles is essential to reduce this preventable burden in Balochistan's vulnerable haemodialysis population.